Hyperuricaemia and essential hypertension: a case control study in Southern Rajasthan - Shrivastav, Chanchal; Sharma, Suman; Suhalka, M. L.; Kaur, Manjinder (International Journal of Research in Medical Sciences, 2016)
Background: Hypertension is one of the current emerging community health problems, which is very common affecting one in four individuals. Hyperuricemia is predictive for the development of both hypertension and coronary artery disease. Since there are various etiological factors associated with hypertension so it is very difficult to predict which one is the most common cause of hypertension. Little or no information is present in the population of Rajasthan, on the association between serum uric acid and essential hypertension. Hence this study is carried out to investigate the existence of an association between serum uric acid and essential hypertension. Methods: In this hospital based case control study, a total of 75 newly diagnosed essential hypertensive cases, 75 prehypertensive cases and 50 normotensive healthy controls, aged 20-50 years of both sexes were enrolled after excluding gout, diabetes mellitus, cardiovascular diseases, renal diseases, metabolic syndrome, secondary hypertension or history of having relevant drugs by taking detailed history and physical examination. Serum uric acid was measured in all study cases as well as control subjects. Results: The results of our study revealed that the mean serum uric acid level and the frequency of subjects with increased serum uric acid level were significantly higher in newly diagnosed cases of essential hypertension as compared to prehypertensive and normotensive controls (p< 0.001). Serum uric acid correlated positively with systolic blood pressure (SBP) (r= + 0.23, p<0.05) and diastolic blood pressure (DBP) (r= + 0.09, p>0.05). These results indicate a definite association between hyperuricaemia and essential hypertension. Conclusions: In the present study, Elevated level of SUA is significantly linked with PreHT and EHT after controlling various confounding factors. The present study showed that the number of hyperuricaemic individuals and mean SUA level were significantly higher in newly diagnosed cases of hypertension as compared to prehypertensive and normotensive control.